A Social Virtual Reality Mobile Application for Learning and Practicing English - Alwafi, Ghadeer Adnan; Almalki, Saliha; Alrougi, Mona; Meccawy, Maram; Meccawy, Zilal (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Many studies promise that virtual reality (VR) applications will be one of the most used tools in foreign language learning. This is because VR keeps learners engaged, motivated, and prepared with better communication skills due to the simulation of real-life environments. As a result of the COVID-19 pandemic and social distancing, it became difficult to use and practice newly learned language skills with real people directly. This paper proposes a social VR mobile application that can be used anytime anywhere to offer a set of different VR environments that simulate real-life situations in order to learn and practice the English language. The application aims to improve speaking skills by offering a private session with a native speaker tutor or a community of learners to practice speaking. It combines the benefits of mobile learning, social networks, and VR. Initial usability testing results showed that the application is simple and easy to use, with some problems discovered and resolved. The application demonstrates that applying VR tools could contribute positively to learning English among the language learners using it.